(untitled) (Journal of Global Accounting, 2026)
This study ascertained the effect of tax planning on the performance of listed consumer goods firms in Nigeria. The specific objective was to determine the effect of effective tax rate, book-tax difference and cash effective tax rate on the return on assets of listed consumer goods firms in Nigeria. The ex-post facto research design was used in the study. Twenty-one listed consumer goods firms in Nigeria made up the population of the study. Purposive sampling was used to select a sample size of sixteen firms that were listed over the period of the study. Secondary data were collected from the annual reports of the sampled firms over a ten year period that spanned 2014 to 2023. In addition to the descriptive and correlational analyses conducted, the hypotheses formulated were tested using Panel Estimated Generalized Least Squares method at a 5% level of significance. The findings showed that: effective tax rate has a positive but non-significant effect on the return on assets of listed consumer goods firms in Nigeria (β = 0.00000108; p = 0.9977); book-tax difference has a significant and positive effect on the return on assets of listed consumer goods firms in Nigeria (β = 0.632595; p = 0.0000); cash effective tax rate has a significant positive effect on the return on assets of listed consumer goods firms in Nigeria (β = 0.006195; p = 0.0008). In conclusion based on findings, tax planning serves not merely as a compliance tool but as a strategic approach to enhance financial stability. The study recommends that financial managers of listed consumer goods firms should focus not only on reducing statutory tax rates but also on optimizing operational efficiency to enhance performance, tax consultants should assist firms in leveraging timing differences between accounting profits and taxable income to maximize financial outcomes without violating tax regulations, and company executives should prioritize effective cash flow management through well-planned tax payment strategies to ensure smooth operations and improved profitability.